A Simulation of Cutting Parameters Influence on Drill Bit and Surface Temperature in Dry Drilling of S45c Carbon Steel - Egano, Junlloyd (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Drilling process on cutting tool temperature distribution is crucial and important to have a clear and exact data to achieve desirable output. Hole quality tends to have percentage of rejection due to the process using blunt bits. This study analyses the temperature phenomenon by the parameters of cutting speed and feed rate and overall identification of the optimum temperature for the drill bit. Material used for this specific study is S45C for the workpiece and model EZ Drill 0800 and DRS for the drill bits and both of the specimen was designed using SOLIDWORKS software with the conversion of STEP. file to proceed in simulation software of both DEFORM-3D and ANSYS. Observation made that the maximum temperature and highest effective stress value for the EZ Drill 0800 is 149℃ and 1610 MPa respectively. As for the DRS, the maximum temperature and highest effective stress value is 83.5℃ and 1736.2 MPa respectively. It was found that the higher amount of cutting speed and feed rate the higher friction forces applied leading to high temperature value. The right amount of value for the parameter could reduce the chances of breakage and bluntness for the overall drilling process.